2014
DOI: 10.3389/fcimb.2014.00001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Vibrio parahaemolyticus in type III secretion system 1 inducing conditions

Abstract: Vibrio parahaemolyticus is an emerging bacterial pathogen capable of causing inflammatory gastroenteritis, wound infections, and septicemia. As a food-borne illness, infection is most frequently associated with the consumption of raw or undercooked seafood, particularly shellfish. It is the primary cause of Vibrio-associated food-borne illness in the United States and the leading cause of food-borne illness in Japan. The larger of its two chromosomes harbors a set of genes encoding type III section system 1 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(140 citation statements)
references
References 87 publications
7
130
3
Order By: Relevance
“…We used RNA-seq analysis to compare the gene expression of E. piscicida grown in DMEM, a condition that mimics bacterial growth during the infection of macrophages, 40,41,42,43 and, to resolve the regulatory role of EsrB, upon EsrB abrogation. These analyses resulted in the finding of a conserved EsrB binding consensus motif in the regulated genes and a repertoire of T3SS-dependent effectors, including 3 established effectors and 6 putative novel effectors that are essential for E. pisicida infection of its host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used RNA-seq analysis to compare the gene expression of E. piscicida grown in DMEM, a condition that mimics bacterial growth during the infection of macrophages, 40,41,42,43 and, to resolve the regulatory role of EsrB, upon EsrB abrogation. These analyses resulted in the finding of a conserved EsrB binding consensus motif in the regulated genes and a repertoire of T3SS-dependent effectors, including 3 established effectors and 6 putative novel effectors that are essential for E. pisicida infection of its host.…”
Section: Discussionmentioning
confidence: 99%
“…DMEM was used to induce the expression of T3SS and T6SS proteins possibly by mimicry of in vivo or intracellular condition. 40,41,42,43 When grown in LB, there was no apparent growth difference between WT and DesrB, whereas in DMEM, the growth of DesrB was markedly faster than that of WT, suggesting a regulatory role of EsrB in E. piscicida metabolic pathways during growth in DMEM (Figs. S1A and S1B).…”
Section: Rna-seq Profiling Of the E Piscicida Transcriptomementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Coutard et al (2007b) found that tdh2 was expressed but not upregulated. On the contrary, Coutard et al (2005) and T3SS2 associated genes (translocator genes and their chaperones, regulators, structural, and effector proteins) showed substantial increases over the course of infection in HeLa cells Nydam et al, 2014;Zhou et al, 2009). …”
Section: Impact Of Nascent and Residual Rna On Virulence Gene Expressmentioning
confidence: 99%
“…T3SS1 appeared to be responsible for the cytotoxicity to several mammalian cell lines (Burdette et al, 2008;Hiyoshi et al, 2010;Nydam et al, 2014;Zhou et al, 2009) and mortality in a mouse model Pineyro et al, 2010).…”
Section: Impact Of Nascent and Residual Rna On Virulence Gene Expressmentioning
confidence: 99%